2017
DOI: 10.1111/sms.12929
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in youth track and field are perceived to have multiple‐level causes that call for ecological (holistic‐developmental) interventions: A national sporting community perceptions and experiences

Abstract: Engaging in competitive sports as a youth can have many health benefits, but recent studies also report a high risk for injury. The long-term purpose of this Swedish research program is to develop a framework for safe track and field training for young athletes (aged 12-15 years). The aim of this study was to establish what is perceived to contribute and cause injuries in youth track and field by compiling the best available experiential knowledge about the underlying factors and use this knowledge to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Training interruptions due to injury or illness lower the chances of reaching high levels of performance substantially, and therefore, better knowledge about injury risk factors and preventative strategies should be of interest to all invested parties. Still, confusion among coaches and parents on how to effectively and safely train growing children has been perceived as one of the important contributing factors to injuries in athletics …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training interruptions due to injury or illness lower the chances of reaching high levels of performance substantially, and therefore, better knowledge about injury risk factors and preventative strategies should be of interest to all invested parties. Still, confusion among coaches and parents on how to effectively and safely train growing children has been perceived as one of the important contributing factors to injuries in athletics …”
Section: Introductionmentioning
confidence: 99%
“…Still, confusion among coaches and parents on how to effectively and safely train growing children has been perceived as one of the important contributing factors to injuries in athletics. 3 Growth and maturation are potential risk factors, unique to the adolescent population. Growth rate is used to describe changes in a physical dimension over a given time and it is typically assessed through anthropometric measures such as stature, body mass, or limb lengths.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that whether a sport organization has a proactive or reactive attitude toward health questions has decisive influence on young sportspeople long‐term progress in settings with high demands on athletic performance 2 . Current research also suggests that a reflective and holistic approach is beneficial for successfully developing talent and to maintain athlete health in child sport 3‐5 . The reason put forward is that due to growth and maturation, children are particularly susceptible to issues associated with their musculo‐skeletal system, hormonal regulation, and psychological makeup when exercising 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A dynamic and strongly interactive approach is therefore required when planning and providing support to talented young sportspeople. In the child athletes’s environment, coaches and parents are the people having the best possibilities to influence a child athlete's development 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation